Jakarta- Bandung High-Speed Rail: A Critical Legal Analysis of Public Policy Formulation - Ipik Permana; Mohamad Taufik Hidayat; Mukarto Siswoyo (PT. Islamic Research Publiser, 2026)
The Jakarta–Bandung High-Speed Rail (KCJB), commercially known as WHOOSH, represents one of Indonesia’s largest strategic infrastructure projects and has generated significant legal and policy debates since its inception. While the project was intended to strengthen national connectivity and promote regional economic growth, its formulation and implementation have raised concerns regarding regulatory consistency, administrative accountability, transparency, public participation, environmental compliance, fiscal governance, and institutional oversight. This study critically examines the KCJB policy from the perspective of public policy formulation by integrating evidence-based policy, public value, policy ethics, and principles of legal governance. Employing a qualitative descriptive case study, the research analyses secondary data derived from legislation, government regulations, official reports, academic publications, judicial and administrative documents, and other authoritative sources. Data were analysed through qualitative content analysis supported by source triangulation. The findings indicate that the formulation of the KCJB policy demonstrates several legal shortcomings. First, the decision-making process reveals weaknesses in regulatory coherence and evidence-based assessment, as reflected in contested feasibility studies and significant project cost escalations that subsequently required changes in financing arrangements. Second, the policymaking process shows limited compliance with fundamental principles of good governance and administrative law, particularly transparency, legal certainty, proportionality, accountability, and meaningful public participation in strategic infrastructure decision-making. Third, the project exposes challenges in ensuring effective legal oversight of state financial commitments and environmental governance, thereby creating potential risks to fiscal accountability and public trust. These findings suggest that the legal legitimacy of strategic infrastructure policies should be evaluated not only in terms of economic efficiency but also through their conformity with constitutional principles, the rule of law, administrative legality, and democratic governance. This study contributes to contemporary legal and public policy scholarship by demonstrating that sustainable infrastructure development requires legal certainty, institutional accountability, and regulatory integrity throughout the policy formulation process.